2016
DOI: 10.1108/edi-11-2015-0092
|View full text |Cite
|
Sign up to set email alerts
|

Making cultural differences matter? Diversity perspectives in higher education

Abstract: Purpose The higher education sector has become increasingly aware of how the increasing diversity in society affects their institutions. The student population has become more diverse and future employers increasingly require trained students who are able to meet the demands of dealing with a more diverse market/clientele. In this regard, education institutions need to align their strategic approach to diversity within their organization. The purpose of this paper is to examine strategical reasons to diversify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Increasingly, academic HRM literature has focused on managing differences in the organization, thus introducing the concept of diversity management (Pitts, 2009;Groeneveld and Van de Walle, 2010), which is defined as the deliberate and conscious effort to stimulate a diverse workforce and manage differences in order to achieve better organizational results (Ely and Thomas, 2001;Pitts, 2009;Groeneveld, 2011). Like the I&L perspective, and in line with Cox and Blake (1991), diversity management is based on the idea that differences between employees should be effectively exploited to foster creativity and innovation in the teams and the organization (Çelik et al, 2014;Meerman et al, 2016;Vos et al, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Increasingly, academic HRM literature has focused on managing differences in the organization, thus introducing the concept of diversity management (Pitts, 2009;Groeneveld and Van de Walle, 2010), which is defined as the deliberate and conscious effort to stimulate a diverse workforce and manage differences in order to achieve better organizational results (Ely and Thomas, 2001;Pitts, 2009;Groeneveld, 2011). Like the I&L perspective, and in line with Cox and Blake (1991), diversity management is based on the idea that differences between employees should be effectively exploited to foster creativity and innovation in the teams and the organization (Çelik et al, 2014;Meerman et al, 2016;Vos et al, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In general, teacher teams have been open to recruiting different teachers and consider this important to meet the needs of student diversity. The study found the value of interaction and joint learning within teams, but did not reveal the value of diversity (VOS, ÇELIK, DE VRIES, 2016).…”
Section: Literature Reviewmentioning
confidence: 63%
“…This is due to the need of employers to have the skill of working with different team members. The needs of the labor market for diversity have a greater degree of influence on the perspective of multiculturalism of teams than just the diversity of the student body (VOS, ÇELIK, DE VRIES, 2016). Therefore, educational institutions need to coordinate strategies, teaching methods for managing cultural diversity (VOS, ÇELIK, DE VRIES, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Part of the cause is the higher outflow among employees of non-Western origin from public organizations than their colleagues of Dutch descent. One popular argument is that employees with a migrant background do not feel at home in these organizations, while another is the lack of transfer possibilities to higher positions in public organizations [6][7]. Binding with the organization they work in is, therefore, considered to be an important objective of the diversity policy of the Dutch public sector.…”
Section: Introductionmentioning
confidence: 99%